ChemInform Abstract: Chemistry and Biochemistry of 13C Hyperpolarized Magnetic Resonance Using Dynamic Nuclear Polarization. Issue 18 (6th May 2014) - Keshari, Kayvan R.; Wilson, David M.
Abstract: Review: 229 refs.